Hubungan Efikasi Diri dengan Pengambilan Keputusan Karir Siswa/I SMA Global Prima National Plus School - Tarigan, Eltalina; Wijaya, Rinna; Chandra, Angelina; Wijaya, Sindy; Ongko, Vinnie; Akmal, Mukhaira El (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2025)
High school students aged 15–18 are in the late adolescence phase and face various challenges in making career decisions, such as pursuing higher education, entering the workforce, or doing both. However, many students experience uncertainty due to low self-confidence, lack of understanding of their interests and talents, and limited experience. This study aims to examine the relationship between self-efficacy and career decision-making among students at Global Prima National Plus School. Using a quantitative correlational approach with a population of 140 students and a saturated sampling technique, data were collected through a Likert scale and analyzed using Pearson correlation with the help of SPSS 27. The results indicate a significant positive relationship between self-efficacy and career decision-making (r = 0.488, p < 0.000). Self-efficacy contributes 23.8% to career decision-making ability, while the remaining 76.2% is influenced by other factors. All respondents demonstrated a high level of career decision-making ability. In conclusion, self-efficacy plays an important role in career decision-making, although other factors such as environment, skills, and personality also have an impact. Enhancing self-efficacy can support students in making better career decisions.